2016
DOI: 10.1007/s00414-016-1430-4
|View full text |Cite
|
Sign up to set email alerts
|

Cranium asymmetry in a modern Greek population sample of known age and sex

Abstract: The aim of this paper is to evaluate and quantify cranium asymmetry, sexual differences in the set of individual asymmetry scores, and the relationship between fluctuating asymmetry and age, in a modern Greek population sample. In addition, we test for the developmental origins of health and disease hypothesis by assessing the correlation between fluctuating asymmetry and cause of death. The study sample consisted of 173 crania of known sex and adult age (92 males, 81 females) belonging to individuals who live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…The current study shows that with respect to a midplane fitted to the shared landmarks (type 0 assessment) or to side landmarks for balancing the two sides (type 1 assessment), asymmetry of the studied human skulls is generally directional, which is consistent with the previous discoveries in the literature (e.g. [ 33 , 34 ]). In general, in the studied population, female skulls appear clearly more asymmetric than male skulls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study shows that with respect to a midplane fitted to the shared landmarks (type 0 assessment) or to side landmarks for balancing the two sides (type 1 assessment), asymmetry of the studied human skulls is generally directional, which is consistent with the previous discoveries in the literature (e.g. [ 33 , 34 ]). In general, in the studied population, female skulls appear clearly more asymmetric than male skulls.…”
Section: Discussionsupporting
confidence: 88%
“…Studies of asymmetry of human skulls have initially used length and angle measurements and lately the Procrustes analysis of landmarks, see, e.g. [ 12 , 17 , 33 35 ]. The current study shows that with respect to a midplane fitted to the shared landmarks (type 0 assessment) or to side landmarks for balancing the two sides (type 1 assessment), asymmetry of the studied human skulls is generally directional, which is consistent with the previous discoveries in the literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although relatively underutilized in DOHaD studies, measures of asymmetry may represent a promising approach to assessing the relationship between developmental stress and health in archeological populations (Chovalopoulou et al, 2017;Weisensee, 2013). A recent study of cranial asymmetry in a modern Greek population found no association between early developmental environments and age at death, as assessed through measures of fluctuating asymmetry (FA) in the cranium (Chovalopoulou et al, 2017).…”
Section: Measures Of Asymmetrymentioning
confidence: 99%
“…Although relatively underutilized in DOHaD studies, measures of asymmetry may represent a promising approach to assessing the relationship between developmental stress and health in archeological populations (Chovalopoulou et al, 2017;Weisensee, 2013). A recent study of cranial asymmetry in a modern Greek population found no association between early developmental environments and age at death, as assessed through measures of fluctuating asymmetry (FA) in the cranium (Chovalopoulou et al, 2017). However, a study of a much larger historical Portuguese population by Weisensee (2013) found an association between FA and cause of death, with more severe FA observed in individuals known to have died from degenerative versus infectious diseases.…”
Section: Measures Of Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation